Inhibition of Pro-inflammatory and Anti-apoptotic Biomarkers during Experimental Oral Cancer Chemoprevention by Dietary Black Raspberries - Oghumu, Steve; Casto, Bruce C.; Ahn-Jarvis, Jennifer; Weghorst, Logan C.; Maloney, Jim; Geuy, Paul; Horvath, Kyle Z.; Bollinger, Claire E.; Warner, Blake M.; Summersgill, Kurt F.; Weghorst, Christopher M.; Knobloch, Thomas J. (Frontiers in Immunology, 2017)
Oral cancer continues to be a significant public health problem worldwide. Recently conducted clinical trials demonstrate the ability of black raspberries (BRBs) to modulate biomarkers of molecular efficacy that supports a chemopreventive strategy against oral cancer. However, it is essential that a preclinical animal model of black raspberry (BRB) chemoprevention which recapitulates human oral carcinogenesis be developed, so that we can validate biomarkers and evaluate potential mechanisms of action. We therefore established the ability of BRBs to inhibit oral lesion formation in a carcinogen-induced rat oral cancer model and examined potential mechanisms. F344 rats were administered 4-nitroquinoline 1-oxide (4NQO) (20 µg/ml) in drinking water for 14 weeks followed by regular drinking water for 6 weeks. At week 14, rats were fed a diet containing either 5 or 10% BRB, or 0.4% ellagic acid (EA), a BRB phytochemical. Dietary administration of 5 and 10% BRB reduced oral lesion incidence and multiplicity by 39.3 and 28.6%, respectively. Histopathological analyses demonstrate the ability of BRBs and, to a lesser extent EA, to inhibit the progression of oral cancer. Oral lesion inhibition by BRBs was associated with a reduction in the mRNA expression of pro-inflammatory biomarkers Cxcl1, Mif, and Nfe2l2 as well as the anti-apoptotic and cell cycle associated markers Birc5, Aurka, Ccna1, and Ccna2. Cellular proliferation (Ki-67 staining) in tongue lesions was inhibited by BRBs and EA. Our study demonstrates that, in the rat 4NQO oral cancer model, dietary administration of BRBs inhibits oral carcinogenesis via inhibition of pro-inflammatory and anti-apoptotic pathways.